Legal Reform Based on Dignified Justice Theory - Teguh Prasetyo (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The people want to understand the concept of law renewal, the general impression is that the meaning or ontology of the concept of law renewal is something like this: "The law is what you change and what you change." Legislative renewal is instead interpreted as the function of law as a tool or instrument (tool) for bringing about change, especially social change. On the other hand, in legal reform, law actually becomes a tool, a parameter, to guide the goals of society. The research method used to create this article is legal research. In general, the intended method of legal research is understood as prescriptive legal research. The theory used to analyze the importance of legal reform is the theory of dignified justice. This research clarified that legal renewal means efforts to bring about change in society using law as a tool (law as a tool for social engineering). In an engineering society, the law does not change, but the direction of change is determined according to the purpose of the law. The theory used to analyze the importance of legal reform is the theory of dignified justice. This research clarified that legal renewal means efforts to bring about change in society using law as a tool (law as a tool for social engineering In an engineering society, the law does not change, but the direction of change is determined according to the purpose of the law.